THE DEVELOPING HISTORY OF TEACHING FOREIGN LANGUAGES AT KARAKALPAK SCHOOLS - Nuratdinova, Nuratdinova (Журнал иностранных языков и лингвистики, 2023)
This thesis discusses the developing of teaching foreign languages in Karakalpakstan. The adoption of a number of decisions to improve the study of foreign languages has expanded the methodological basis for the teaching of foreign languages in educational institutions in Karakalpakstan.